Exploration of Community Empowerment in Koanara Village as the Entrance to the Kelimutu National Park - Saldanah Neno, Marianus; Jehamat, Lasarus; Jelahut, Yosep Emanuel; Aman, Dominikus Kopong Toni (Journal of Business Management and Economic Development, 2023)
community empowerment is an effort to develop self-sufficiency and community welfare by increasing knowledge, attitudes, skills, behavior, abilities, awareness, and utilizing existing resources through the establishment of policies, programs, activities, and assistance that are in accordance with the root of the problem. The purpose of this research is to explore community empowerment activities in supporting villages of the Kelimutu National Park, especially Koanara village as the entrance to the Kelimutu National Park (TNK). In order to obtain comprehensive data, a case study approach was used with data collection techniques of interviews, observation and documentation. The data analysis technique used is descriptive qualitative. Data analysis is done by organizing the data, describing it in units, synthesizing it, compiling it into patterns, choosing which ones are important and what will be studied, and making conclusions. The research results found that there were several empowerment activities in KNP supporting villages, especially Koanara villages such as The Mandiri Tourism in the National Community Empowerment Program (PNPM) received a positive response from the community. Apart from that, there are also several local community empowerment activities that have arisen from local and village government initiatives as well as by the Koanara village community itself, such as establising of tourism awareness groups: The Moni Kelimutu Tourism Association (P3MK) gave birth to actors in lodging businesses, transportation services, restaurants, cafes and art galleries; village-owned enterprise (BUMDES) Hapo Kalo Koanara Village empowers village communities in agriculture and agro-tourism; and BUMDES with Kelimutu. Bumdes Kelimutu belongs to 9 villages in the Kelimutu sub-district. There are 3 business units that are formed, namely the Coming Business Unit, the Tourism Unit and the Savings and Loans Unit.